Innovation in Numeracy Learning through the Make a Match Method Based on Local Wisdom of Malang for Children Aged 4-5 Years - Maria Mu’ini Christya Sunoto; Dedi Kuswandi; M. Arafik (Institut Agama Islam Negeri Madura, 2025)
Numeracy learning from an early age is the foundation for students' academic success at the next level of education. However, current numeracy learning is still one-way, focused on memorizing numbers, so it does not provide meaningful experiences for students. This study aims to analyze the application of the Make a Match method based on Malangan local wisdom in numeracy learning for students aged 4-5 years. The research method uses a descriptive qualitative approach through participatory observation techniques, in-depth interviews, and documentation at Dharma Wanita Kindergarten, Malang Regency. The results of the study revealed that the application of the Make a Match method based on Malangan local wisdom succeeded in transforming numeracy learning. Success is reflected in the enthusiasm of students in participating in learning that integrates Malangan Masks and batik motifs into numeracy materials. Supporting factors include the creativity of educators in developing learning media and collaboration with local artists. Inhibiting factors include limited preparation time and the lack of cultural references that suit the characteristics of early childhood students. Recommendations for program development include ongoing training for educators related to cultural integration into learning and the preparation of a local cultural database that has been adapted for early childhood learning.